Coronavirus infection and immune system: An insight of COVID-19 in cancer patients. (September 2020) - Indini, Alice; Rijavec, Erika; Ghidini, Michele; Bareggi, Claudia; Cattaneo, Monica; Galassi, Barbara; Gambini, Donatella; Grossi, Francesco
Highlights: There is limited data on the novel coronavirus respiratory illness (COVID-19) in patients with cancer. COVID-19 diffusion in cancer patients is not prominent as expected, rather seems as contagious as for the general population. There is no clear role for immune-suppression as an additional risk factor for coronavirus infection. The pathogenicity of COVID-19 is exacerbated by the host's immune system's reaction. Patients receiving immunotherapy may be more at risk for an aberrant response in case of infection. Abstract: The novel coronavirus respiratory illness (COVID-19) is a public health emergency of global concern. Patients with cancer are at high risk of infections, due to an overall immunocompromised status. However, this connection is not straightforward for coronavirus (CoV) infection, in which the host immune response is the main driver of tissue damage. We performed a thorough review of data on CoV pathogenesis and morbidity rate in cancer patients, through the analysis of the previous CoV pandemics. Considering the interaction between CoV and the host immune system, cancer patients receiving immunotherapy might be more at risk for an aberrant immune response in case of infection, and might therefore deserve additional precautions. The limited available data do not allow us to provide practical indications for the management of cancer patients in this critical situation. Efforts should be made to prospectively collect data, to identify effective interventions to guide treatment decision.